Humidity effect on electromechanical breakdown of dielectric elastomers subject to a ramp voltage - Zuo, Yuchen; Huang, Zihuan; Zhang, Junshi; Liu, Lei; Zhu, Jihong; Zhang, Weihong (Smart materials and structures, 2024)
As is known, the external excitations, material parameters, and ambient environment may affect the electromechanical properties of dielectric elastomers (DEs), which directly induce the occurrence of electrical breakdown. In this paper, we experimentally and theoretically studied the effects of voltage ramp rate, ambient humidity, electrode material, and pre-stretch on electromechanical deformation and electrical breakdown of DEs. By coupling the above four factors, the nonlinear constitutive model and electrical breakdown model of the viscoelastic DE are developed, which are shown to be consistent with the experimental observations. Firstly, when the ramp voltages with different rate are loaded to the same value, a larger voltage ramp rate leads to a smaller stretch and a higher electrical breakdown field strength of the elastomer. Besides, as the humidity increases, the electromechanical deformation increases and the electrical breakdown field decreases. In addition, it is found that different electrode materials show diverse sensitivity to the electromechanical deformation and breakdown field. Finally, with the increase of the pre-stretch from 2 to 4, the deformation and breakdown field both show an upward trend.